Studying Cities in their Context - de Vries, Jan (Urban History Review / Revue d'histoire urbaine, 1990)
Urban historians have not transcended a fascination with specific places. Consequently, this field of historical inquiry has a relative lack of theoretical statements concerning sets of cities. Meanwhile, social scientists clearly have advanced many valuable theories and methods for the study of groups of cities; however, they largely have been concerned with projects of rationalization and models of modernization which truncate the past. This article suggests how definitions of urbanization, a few fundamentals of urban demography and geography, and theoretical analysis of urban functions and culture can help to define sets of cities while retaining the historian's sense of changes over time.